Les femmes qui furent les premières à raconter Auschwitz à l’Italie - Elisabetta Ruffini (Laboratoire Italien)
In the Italy that came out of the war, not unlike what was happening in other European nations, there was little room for the voices of deportees. The construction of a public space for the narration of the deportation experience was a challenge that played out both at the level of the imaginary and at the level of collective awareness. While the impact of the recent war was being fixed in the collective memory, seven women raised their voices from the shadows of rhetoric and were the first to recount the story of Auschwitz in Italy. They decided to immediately bear witness and share the stories of their companions who had not returned, their loved ones who had not survived, and their friends who had been murdered. Two of these women, as seen in notebooks collected from the rubble of Germany, which they crossed on their return journey, started writing as early as May 1945. Some found their homes and loved ones, others had to start afresh. They all chose to publish their writings immediately, some through small publishing houses, in which they addressed some of the major themes of the genre: the central role the body holds in describing the experience, the relationship to literature, the delegated narrator, the collective autobiography. This text is dedicated to these pioneering authors of Italian literature that focused on the concentration camp experience.